Best-practice prevention alone or with conventional or biological caries management for 3- to 7-year-olds: the FiCTION three-arm RCT - Maguire, Anne; Clarkson, Jan E; Douglas, Gail VA; Ryan, Vicky; Homer, Tara; Marshman, Zoe; McColl, Elaine; Wilson, Nina; Vale, Luke; Robertson, Mark; Abouhajar, Alaa; Holmes, Richard D; et al. (Health technology assessment (Winchester, England), 2020)
Historically, lack of evidence for effective management of decay in primary teeth has caused uncertainty, but there is emerging evidence to support alternative strategies to conventional fillings, which are minimally invasive and prevention orientated. The objectives were (1) to assess the clinical effectiveness and cost-effectiveness of three strategies for managing caries in primary teeth and (2) to assess quality of life, dental anxiety, the acceptability and experiences of children, parents and dental professionals, and caries development and/or progression. This was a multicentre, three-arm parallel-group, participant-randomised controlled trial. Allocation concealment was achieved by use of a centralised web-based randomisation facility hosted by Newcastle Clinical Trials Unit. This trial was set in primary dental care in Scotland, England and Wales. Participants were NHS patients aged 3-7 years who were at a high risk of tooth decay and had at least one primary molar tooth with decay into dentine, but no pain/sepsis. Three interventions were employed: (1) conventional with best-practice prevention (local anaesthetic, carious tissue removal, filling placement), (2) biological with best-practice prevention (sealing-in decay, selective carious tissue removal and fissure sealants) and (3) best-practice prevention alone (dietary and toothbrushing advice, topical fluoride and fissure sealing of permanent teeth). The clinical effectiveness outcomes were the proportion of children with at least one episode (incidence) and the number of episodes, for each child, of dental pain or dental sepsis or both over the follow-up period. The cost-effectiveness outcomes were the cost per incidence of, and cost per episode of, dental pain and/or dental sepsis avoided over the follow-up period. A total of 72 dental practices were recruited and 1144 participants were randomised (conventional arm, = 386; biological arm, = 381; prevention alone arm, = 377). Of these, 1058 were included in an intention-to-treat analysis (conventional arm, = 352; biological arm, = 352; prevention alone arm, = 354). The median follow-up time was 33.8 months (interquartile range 23.8-36.7 months). The proportion of children with at least one episode of pain or sepsis or both was 42% (conventional arm), 40% (biological arm) and 45% (prevention alone arm). There was no evidence of a difference in incidence or episodes of pain/sepsis between arms. When comparing the biological arm with the conventional arm, the risk difference was -0.02 (97.5% confidence interval -0.10 to 0.06), which indicates, on average, a 2% reduced risk of dental pain and/or dental sepsis in the biological arm compared with the conventional arm. Comparing the prevention alone arm with the conventional arm, the risk difference was 0.04 (97.5% confidence interval -0.04 to 0.12), which indicates, on average, a 4% increased risk of dental pain and/or dental sepsis in the prevention alone arm compared with the conventional arm. Compared with the conventional arm, there was no evidence of a difference in episodes of pain/sepsis among children in the biological arm (incident rate ratio 0.95, 97.5% confidence interval 0.75 to 1.21, which indicates that there were slightly fewer episodes, on average, in the biological arm than the conventional arm) or in the prevention alone arm (incident rate ratio 1.18, 97.5% confidence interval 0.94 to 1.48, which indicates that there were slightly more episodes in the prevention alone arm than the conventional arm). Over the willingness-to-pay values considered, the probability of the biological treatment approach being considered cost-effective was approximately no higher than 60% to avoid an incidence of dental pain and/or dental sepsis and no higher than 70% to avoid an episode of pain/sepsis. There was no evidence of an overall difference between the three treatment approaches for experience of, or number of episodes of, dental pain or dental sepsis or both over the follow-up period. Recommendations for future work include exploring barriers to the use of conventional techniques for carious lesion detection and diagnosis (e.g. radiographs) and developing and evaluating suitable techniques and strategies for use in young children in primary care. Current Controlled Trials ISRCTN77044005. This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in ; Vol. 24, No. 1. See the NIHR Journals Library website for further project information.